2019
DOI: 10.1002/ece3.5418
|View full text |Cite
|
Sign up to set email alerts
|

Species‐level repertoire size predicts a correlation between individual song elaboration and reproductive success

Abstract: Birdsong has long been considered a sexually selected trait that relays honest information about male quality, and laboratory studies generally suggest that female songbirds prefer larger repertoires. However, analysis of field studies across species surprisingly revealed a weak correlation between song elaboration and reproductive success, and it remains unknown why only certain species show this correlation in nature. Taken together, these studies suggest that females in numerous species can detect and prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 124 publications
1
13
2
Order By: Relevance
“…In the language of birdsong literature, this would be a more syntactically complex song than one composed of a single repeated note. Like trill rate, syllable and song complexity has been shown to play a role in mate attraction for some species, although the strength and ubiquity of this effect is contested (see meta-analyses by [13,64] ). For example, female Bengalese finches prefer songs with higher complexity, but stressful conditions early in life limit a male's syntactical complexity, indicating that these songs are more difficult to produce (large α) [65] .…”
Section: Application To Specific Birdsong Characteristicsmentioning
confidence: 99%
“…In the language of birdsong literature, this would be a more syntactically complex song than one composed of a single repeated note. Like trill rate, syllable and song complexity has been shown to play a role in mate attraction for some species, although the strength and ubiquity of this effect is contested (see meta-analyses by [13,64] ). For example, female Bengalese finches prefer songs with higher complexity, but stressful conditions early in life limit a male's syntactical complexity, indicating that these songs are more difficult to produce (large α) [65] .…”
Section: Application To Specific Birdsong Characteristicsmentioning
confidence: 99%
“…Song repertoire is defined as the number of unique songs sung by an individual (Robinson & Creanza, 2019). Song repertoire sizes can differ greatly between species, ranging anywhere from a few songs to thousands of songs (Vargas‐Castro et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In many species of songbirds, complex vocalizations serve as a sexual display to attract mates or as territorial display against conspecific and heterospecific individuals. It has been shown that individuals with larger repertoire sizes are more successful in attaining mates (Catchpole 1987; Robinson and Creanza 2019) or can hold a territory for a longer duration (Hiebert et al 1989). It has also been reported that in several species the size of the repertoire increases with complexity in vocalization context.…”
Section: Introductionmentioning
confidence: 99%